Unlocking environmental harmony through export earnings: exploring the impact of remittances and infrastructure growth - Yi, Xiaoming; Qamruzzaman, Md (Frontiers in Environmental Science, 2024)
This research addresses the intricate relationship between economic growth, remittances, export earnings, infrastructural development, and environmental sustainability in Bangladesh from 1990 to 2020. Utilizing the Environmental Kuznets Curve (EKC) hypothesis, unit root tests, cointegration analysis, and advanced time-series modeling techniques like ARDL and NARDL, the study investigates the impacts of these factors on environmental outcomes. The findings reveal that while economic growth initially exacerbates carbon emissions and ecological degradation, further development leads to environmental improvements, validating the EKC hypothesis. Remittances are found to significantly increase carbon emissions and ecological degradation, suggesting that policy measures are needed to manage their environmental impact. Conversely, technological innovation shows a negative correlation with carbon emissions and ecological footprint, underscoring its role in promoting sustainable development. Export earnings and infrastructural development, however, demonstrate mixed effects on environmental sustainability, with evidence suggesting that infrastructural growth may lead to environmental degradation. The study's insights are critical for policymakers aiming to balance economic growth with environmental sustainability, advocating for targeted interventions to mitigate the environmental consequences of remittance inflows and promote technological innovation aligned with sustainable development goals.This research explores the complex connections between economic growth, environmental sustainability, and remittances in Bangladesh. From 1990 to 2020, our investigation employs a multifaceted approach, incorporating the Environmental Kuznets Curve (EKC) hypothesis, unit root tests, cointegration analysis, and advanced time-series modeling techniques. The analysis shows an initial link between economic growth, increased carbon emissions, and ecological degradation. However, further economic development leads to environmental improvement once a certain threshold is reached, supporting the EKC hypothesis. The study also finds that remittances significantly impact environmental outcomes, with an increase in REM correlating with higher carbon emissions and ecological degradation. This confirms concerns raised in previous research. Notwithstanding, TI is found to have a negative correlation with carbon emissions and ecological footprint, highlighting the importance of promoting innovation for sustainable development. Causality analyses further deepen our understanding of the relationships between economic variables and environmental outcomes, providing valuable insights for policymakers. The findings of this research have important policy implications. Bangladesh needs targeted policies to balance economic prosperity and environmental stewardship.